Improving the quality of diagnosis of maxillomandibular anomalies on the background of chronic habits - Makhlynets Н. П.; Ozhohan З. Р.; Pantus А. В. (Actual Dentistry, 2023)
The aim of the study. Improving the effectiveness of the diagnosis of maxillomandibular anomalies among the patients with pathological occlusion, existing bad habits is relevant due to the spread of social stress among young people and the searc for its compensation through the development of bad habits. Research methods. We conducted clinical and radiological methods of examination of 60 patients aged 15–17 with acquired maxillomandibular anomalies, deformities, and 15 people in the comparison group. We studied the data of computer tomograms, performed stereotopometric analysis (threedimensional cephalometry), determination of the thickness of the masticatory muscles in symmetrical areas of the face. Patients underwent a secret questionnaire to identify stressors that affected the body, studied the relationship between th epresence of stress and the appearance of changes in cephalometric parameters. Scientific novelty. Clinical studies and survey results have shown that 95 % of patients surveyed have bad habits that are associated with chronic social stress. The results of examination of cephalometric analysis and photoprotocol confirm the expressed disproportions of one of the jaws, where there is a oral habit; confirm the presence of acquired rather than congenital deformity of the facial skeleton, which is associated with changes in the thickness of the masticatory muscles on the side of the deformation. Conclusions. Our research has shown that bad habits progress in the presence of chronic social stress, which according to the survey results in 95% of patients. Distance learning is the most important stress factor in most patients surveyed.3D cephalometric analysis should be included in the mandatory methods for the diagnosis of acquired deformities of the maxillofacial area. Clinical and radiological research methods help the orthodontist to identify a whole range of interrelated etiological factors in the development of dental anomalies and acquired deformities of the maxillofacial area and make a correct plan of complex treatment.